Application of digital holographic microscopy to evaluate the dynamics of a single red blood cell influenced by low-power laser light. (October 2021) - Kucharski, Dawid; Bartczak, Monika
Highlights: Light from a Low-Level-Laser-Therapy scanner is invasive for erythrocyte dynamics. A coherent red light strongly impacts the cells drift speed. A standard deviation is a sensitive statistical marker of the erythrocyte dynamics. An open-source image processing algorithm is essential for data reproduction. The light-cell interaction was studied because of the everyday use of LLLT scanners. Abstract: In the paper, a shift of individual human erythrocytes drifts speed, stimulated by various low-power lasers irradiation, was studied by digital holographic microscopy (DHM). Well known in physiotherapy, a low-level-laser-therapy (LLLT) scanner was used as the stimulation light source, with diode and He-Ne lasers to compare. In the article, an open-source image processing algorithm for simultaneous dynamics and geometrical properties evaluations of the red blood cells is proposed. A strong influence of the low-level red light on the red blood cells dynamics was observed. The effect is important for a better understanding of the laser treatment mechanism. The proposed phase image analysis algorithm significantly improves the individual cells tracing precision for a life science application. The programme might be useful for optical tweezer, imaging flow cytometry, or high precision cells-photon interaction research.